SUPERVISI PENDIDIKAN ISLAM BIMBINGAN DAN KONSELING DI SEKOLAH SEBAGAI BAGIAN SUPERVISI PENDIDIKAN - Ngaini, Sovi Ul; Athi, Fina Umu Rif; Sabilarrizqi, Zidna; Farhah, Umi; Farisi, Muhammad Salman Al; Muzakki, Arriza Ahmad Zain (Jurnal Manajemen Pendidikan, 2025)
This study aims to explore the role of guidance and counseling (GC) services as part of Islamic educational supervision at SMK Syubbanul Wathon. Supervision in Islamic education encompasses not only academic and administrative aspects but also moral and spiritual development of students. The study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, field observations, and document analysis involving guidance counselors, school principals, and subject teachers. The findings reveal that GC services are well integrated into the school's supervision program, emphasizing Islamic approaches in guiding students through personal, social, and academic challenges. Guidance counselors play a strategic role in shaping student character based on Islamic and humanistic values. The school principal is also actively involved in supervising and supporting the implementation of GC services to create a religious and conducive school environment. This study shows that the integration of GC into Islamic educational supervision has a positive impact on students' character development and the overall learning climate. The novelty of this research lies in the systematic integration of guidance and counseling services within Islamic educational supervision at the vocational school level.